1990
DOI: 10.1037/0022-3514.59.3.525
|View full text |Cite
|
Sign up to set email alerts
|

Coping as a personality process: A prospective study.

Abstract: The study tested the proposition that coping is personality in action under stress. Using a stressful medical school entrance examination, the study examined (a) whether neurotieism emerged in coping patterns over time and (b) whether the influence of neurotieism on coping accounted for changes in anxiety and examination performance. Fifty premedical students reported their coping efforts at 35 days before, 10 days before, and 17 days after the examination. They provided daily reports of anxiety for 35 days su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

39
393
2
20

Year Published

1992
1992
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 541 publications
(454 citation statements)
references
References 31 publications
39
393
2
20
Order By: Relevance
“…Individuals with high neuroticism have been reported to have higher levels of anger and depression when faced with interpersonal conflict than individuals with low neuroticism (Bolger and Zuckerman, 1995), as well as larger increases in anxiety in response to stressful events (Bolger, 1990). Personality researchers have long maintained that neuroticism is a vulnerability marker for depression and other comorbid psychiatric disorders (Khan et al, 2005;Ormel et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with high neuroticism have been reported to have higher levels of anger and depression when faced with interpersonal conflict than individuals with low neuroticism (Bolger and Zuckerman, 1995), as well as larger increases in anxiety in response to stressful events (Bolger, 1990). Personality researchers have long maintained that neuroticism is a vulnerability marker for depression and other comorbid psychiatric disorders (Khan et al, 2005;Ormel et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…This is noteworthy in light of the evidence linking Neuroticism with less adaptive coping strategies, such as behavioral disengagement, wishful thinking, and self-blame (Bolger, 1990;Carver et al, 1989;Connor-Smith & Flachsbart, 2007).…”
Section: Coping Styles and Personalitymentioning
confidence: 92%
“…Studying coping in relation to personality has been conducted with the Five Factor Model of personality, and relationships have been found with Vulnerability to Stress, one of the facets of the Neuroticism dimension (Costa & McCrae, 1985). Subsequent study has shown Neuroticism to predict numerous maladaptive coping strategies, such as wishful thinking, self-blame, withdrawal, and escapeavoidance (Bolger, 1990;Connor-Smith & Flachsbart, 2007;O'Brien & DeLongis, 1996), although causal relationships have been debated (see Bolger, 1990). …”
Section: Coping Styles and Personalitymentioning
confidence: 99%
See 1 more Smart Citation
“…Since the stress posed by arthritis is chronic, an individual's disposition may play a critical role in the coping process. Some studies of individuals coping with other MANNE AND ZAUTRA life stressors have suggested that certain personality traits, including neuroticism, predict coping choices (36). For example, in arthritis patients, internal locus of control has been related to active coping (17) and neuroticism has been associated with wishful thinking and catastrophizing (37).…”
Section: Issues Of Methodology and Theorymentioning
confidence: 99%